The development of knowledge-shelf to enable an effective set-based concurrent engineering application - Suwanda, Supriana; Al-Ashaab, Ahmed; Beg, Najam (Inderscience, 2020)
This paper presents the development of knowledge-shelf (K-shelf) concept to enable set-based concurrent engineering (SBCE) application via knowledge provision. Three main outcomes are presented: 1) concept of the K-shelf in supporting designers throughout SBCE process; 2) demonstrates the concept via web-based software; 3) an industrial case study of surface jet pump (SJP) is also presented to validate the K-shelf concept and its software demonstrator. The K-shelf capabilities of capturing and storing design rationale in a well-structured manner and to support the comparisons among set of design solutions are the main focus of this paper.
Keywords: SJP; surface jet pump; TOC; trade-off curve; design rationale; knowledge-shelf; set-based concurrent engineering